The Influence of Gender and Anthropometry on Haemodynamic Status at Rest and in Response to Graded Incremental Head-Up Tilt in Young, Healthy Adults - Sarafian, Delphine; Miles-Chan, Jennifer L. (Frontiers in Physiology, 2017)
The body’s ability to rapidly and appropriately regulate blood pressure in response to changing physiological demand is a key feature of a healthy cardiovascular system. Passively tilting the body, thereby changing central blood volume, is a well-recognised and controlled method of evaluating this ability. However, such studies usually involve single tilt angles, or intermittent tilting separated by supine, resting periods; valuable information concerning the adaptive capacity of the regulatory systems involved is therefore currently lacking. Furthermore, despite increasing recognition that men and women differ in the magnitude of their haemodynamic response to such certain stimuli, little is known about the degree to which gender differences in body composition and anthropometry influence these regulatory pathways, or indeed if these differences are apparent in response to graded, incremental tilting. In the present study we measured, in 23 young, healthy adults (13 men, 10 women), the continuous beat-to-beat haemodynamic response to graded, incremental tilting (0°, 20°, 40°, 60°, and back to 40°) with each tilt angle lasting 16 min. On average, we observed increases in heart rate (+41%), blood pressure (+10%) and total peripheral resistance (+16%) in response to tilting. However, whilst men showed an immediate decrease in cardiac output upon tilting (-8.9%) cardiac output in women did not change significantly from supine values. Interestingly, the decrease in stroke volume observed in women was significantly less than that observed in men (-22% versus -36%, p<0.05); although the present study could not determine if this difference was due to gender per se or due to differences in body size (in particular height) between the two gender groups. Such disparities in the magnitude of autonomic response may indicate (in the case of our gradual incremental tilt procedure) a better buffering capacity to progressive changes in central blood volume in women; which warrants further investigation, particularly in light of the well-recognized differences in cardiovascular disease risk between men and women.